Opportunistic intestinal parasite infection and mode of sexual intercourse of HIV-infected patients in the era of HAART - Viroj Wiwanitkit (2018)
One of the major health problems among HIV-infected patients is the intestinal parasite infestations. At present, opportunistic intestinal parasite infection is very common in patients with HIV/AIDS and remains a treat to public health. Association of HIV infection with gut parasites is likely to be related to sexual modes of contact that favour both HIV and the parasite. A cross-sectional study to determine the correlation between opportunistic intestinal parasite infection and mode of sexual intercourse among HIV/AIDS patients was conducted. In the study of 40 HIV/AIDS adult patients with diarrhea, a total of 38 cases with heterosexual mode of intercourse and 2 with homosexual mode of intercourse were reported during the study period. Of interest, there is no association between opportunistic intestinal parasite infection and mode of sexual intercourse of HIV-infected patients (P value > 0.05). © 2006 Springer Science+Business Media, LLC.